Fingerprint recognition using feature extraction - Izni Syarinaz, Ismayuddin (2006)
Lately,fingerprint recognition usage among users is to make sure the safety of security level or pin code user is very encourage.There are so many applications that using fingerprint recognition such as fingerprint recognition for password and it is also used in order to recognize individual identity card.However,the fingerprint among individual is so unfamiliar and not for common known. Throughout this project,'Fingerprint Recognition using Feature Extraction'can recognize the types of fingerprint for every individual and the unique is,with every characteristics of the difference fingerprint among individual,it can be read in computer language by using the method that was shown in image processing.The reason why this system was developed is to analyze the method that always been used to recognize fingerprint.Besides that, fingerprint recognition from analog image into digital image can be carry out by using feature extraction method that is can recognize the characteristic in fingerprint image.